Exploring the Health Benefits and Therapeutic Uses of Amruthotharam Kashayam (International Journal of Ayurveda and Pharma Research, 2025)
Amruthotharam kashayam, or Nagaradi Kashayam, is prepared with three herbal remedies; Haritaki (Terminalia chebula), Shunti (Zingiber officinale), and Guduchi (Tinospora cordifolia) in 6:4:2 ratio. This formulation has the potential to treat numerous diseases. Comparing to the other drugs, the proportion of Amritu is higher than Nagara and Harithaki, hence the name Amruthotharam Kashayam. In various diseases with different Anupanas it is highly beneficial. Amruthotharam kashayam is an amazing formulation mentioned under Kashaya Prayoga prakarana. Through the qualities of Rasapanchaka and the synergistic impact of ingredients, Amruthotharam Kashayam effectively reduces Ama and raises Agni. When used logically with the right Anupanas, Amruthotharam Kashayam produces amazing results for a wide range of illnesses. According to classical literature, its Anupana is Saindhava (rock salt) and Guda (jaggery). However, this Kashayam can be made more effective by combining it with other medications during preparation, as in Anaha and Gulma- with Hinguvachadi choornam. Because Hinguvachadi choornam is mentioned in both Agnimandya and Amadosha, it will have an additional effect. Since Amrithotharam Kashayam possesses the properties of Amapachana, it is strictly prohibited to be consumed with Ghrita. Avarti tailas are also contraindicated due to their Guruta (heaviness). In Ayurvedic treatment, Amruttotaram kashayam is frequently used as a stand-alone medication for a variety of ailments.